2021
DOI: 10.1177/23259671211000764
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Passive Shoulder Range of Motion Between Baseball Players With Neurogenic Thoracic Outlet Syndrome and Matched Healthy Controls

Abstract: Background: Neurogenic thoracic outlet syndrome (nTOS) is becoming more recognized as a diagnosis in the throwing athlete. Currently, there is limited information on the clinical presentation and development of nTOS in baseball players. Purpose: To compare passive shoulder range of motion (ROM) and anatomic humeral retrotorsion (HRT) of baseball players diagnosed with nTOS with a group of healthy, matched controls. Study Design: Cross-sectional study; Level of evidence, 3. Methods: A total of 53 adolescent bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…They also report activity-related fatigue including decreasing pitch velocity, distal upper extremity numbness, paresthesia, and weakness. Garrison et al 14 reported that adolescent baseball players with a diagnosis of NTOS had significantly less external rotation of the affected shoulder compared with healthy matched controls.…”
Section: -In-5mentioning
confidence: 99%
“…They also report activity-related fatigue including decreasing pitch velocity, distal upper extremity numbness, paresthesia, and weakness. Garrison et al 14 reported that adolescent baseball players with a diagnosis of NTOS had significantly less external rotation of the affected shoulder compared with healthy matched controls.…”
Section: -In-5mentioning
confidence: 99%
“…A number of studies have looked at factors related to injury in the youth baseball population over the past year ranging in topics from; early sport specialization (ESS) (12)(13)(14)(15)(16), pitch counts (17)(18)(19)(20)(21)(22)(23), prethrowing protocols (24,25), imaging findings (26), to body region-specific inquiries (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43) in search for opportunities to reduce the risk of injury in this population. We will review a wide range of articles and their relevance to injury risk in this population.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Numerous studies have investigated normative values for shoulder strength and range of motion in the throwing shoulder and their relation to upper extremity injury (30)(31)(32)34). Descriptive profiles of youth baseball players (ages 5 to 12.9 years) have been established for shoulder internal rotation and external rotation passive range of motion, total arc and shoulder internal and external rotation strength at neutral and 90 degrees abduction (34).…”
Section: Shouldermentioning
confidence: 99%
See 1 more Smart Citation